Enhancing Critical Reasoning Character in Pancasila Students: A STEAM Approach by E-Module PRISMA - Esty Setyo Utaminingsih; Abu Anwar; Arbi Arbi; Carolina Lala; Mahi Sultan Salama; Muhamad Subhi Apriantoro; Belita Yoan Intania; Aldi Ihsandi (Postgraduate, University of Mataram, 2024)
This study aimed to assess the Prisma e-module's impact on elementary school students' critical reasoning abilities. A pre-experimental Pretest Posttest Control Group Design was employed. Two groups—experimental and control—received different treatments. The experimental group used e-modules, while the control group relied on books. Pre- and post-treatment tests were conducted to evaluate the e-module's effect. An Independent Sample t-test was used to compare the two groups, with results showing a Sig. (2-tailed) value of 0.000, leading to the rejection of H0 and acceptance of Ha. The N-Gain test measured improvements in various critical reasoning elements. The experimental group showed significant improvement, with the highest N-Gain of 0.74 in